The impact of treating parental anxiety on children's mental health: An empty systematic review. (May 2022) - Chapman, Laura; Hutson, Rosie; Dunn, Abby; Brown, Maddy; Savill, Ella; Cartwright-Hatton, Sam
Abstract: Children of anxious parents are at heightened risk of developing an anxiety disorder of their own, but promising research indicates that targeting parenting behaviours can reduce the risk of intergenerational transmission of anxiety. Given there is extensive evidence for the efficacy of treatments for adult anxiety, the current review sought to identify whether interventions solely addressing parental symptoms had any effect on the mental health and wellbeing of their children. Randomised Controlled Trials of psychological interventions targeting adults with a probable anxiety disorder and which included a child mental health or wellbeing outcome were eligible for inclusion. Scopus, Web of Science, PubMed, PsychINFO, and PsychArticles were searched, and 2137 articles were systematically reviewed. However, no articles were identified that met the review criteria. Research into interventions targeting adult anxiety is failing to consider the potential benefit treatment may have on dependent children. This is a missed opportunity to evaluate a potential means of support for children who are known to be at risk of anxiety. Evaluation of psychological interventions for adult anxiety should consider including both adult and child mental health outcomes to determine potential preventative effects. Highlights: Children of anxious parents are at increased risk of developing anxiety disorders. There are many well-evaluated interventions for treating adult anxiety. It is unknown whether treatment of parental anxiety reduces anxiety in children.